Canine Genetics and Epidemiology - Ollier, Bill; Aguirre, Gustavo; Kennedy, Lorna
Canine Genetics and Epidemiology is a peer-reviewed, open access journal addressing genetic, genomic and epidemiological research in both domestic and wild canids, relating to breed and species diversity, and canine evolution. This international journal aims to disseminate research not only between scientists, but also to inform veterinarians, dog breeders and owners. To encourage the public understanding of science, each published article will include an extended lay summary plus key “take home messages” for non-specialists and an educated lay readership. Canine Genetics and Epidemiology focuses on the following areas: Canine monogenic and complex disease genetics, genomics and epidemiology Canine- human comparative disease genetics/genomics Domestic dog breed genetics and breed diversity Canine evolutionary genetics Canine wildlife conservation genetics and biology Dog/canine immunogenetics and MHC diversity Canine genetics and physiology Morphological and behavioral genetics Epidemiological studies of canine health and disease Canine gene-phenotype relationship Gene-gene and gene-environment interactions in canids The journal will not publish articles describing research generated through experimental procedures that inflict pain and suffering to animals.